Vinculação da parte não signatária à cláusula compromissória: o caso dos grupos societários à luz do ordenamento jurídico brasileiro - Azevedo, Ciro Rangel (2017)
The purpose of the present paper is to analyze the phenomenon related to the binding of a non-signatory party to the arbitration agreement in the context of group of companies under the Brazilian legal system. Therefore, starting from the Brazilian legal framework of the arbitration agreement under the brazilian law nº 9.307/1996 and also a legal evaluation based on principles and arbitral and Brazilian court’s precedents, this paper seeks to comprehend the concept and extent of the non-signatory consent, which is the fundamental element to impose the binding effect. In this context, it will be comprehended the role carried out by the non-signatory party along the negotiation, execution and/or termination of the contract in which other company of the same group of companies celebrated with another party. The behavior adopted by the non-signatory party, though, may indicate the implied consent to the contract and to the arbitration provision inserted, justifying binding effect of the arbitration procedure upon the mentioned non-signatory party. However, the simple existence of a group of companies does not authorize immediately the binding effect, but generates the relative presumption of the non-signatory company’s consent. In conclusion, this paper indicates that is possible to bind a non-signatory party in the context of group of companies under Brazilian legal system